Asteroseismology of low-mass stars: the balance between partial ionization and Coulomb interactions. Issue 4 (4th September 2021) - Brito, Ana; Lopes, Ilídio
ABSTRACT: All cool stars with outer convective zones have the potential to exhibit stochastically excited stellar oscillations. In this work, we explore the outer layers of stars less massive than the Sun. In particular, we have computed a set of stellar models ranging from 0.4 to 0.9 M⊙ with the aim at determining the impact on stellar oscillations of two physical processes occurring in the envelopes of these stars. Namely, the partial ionization of chemical elements and the electrostatic interactions between particles in the outer layers. We find that alongside with partial ionization, Coulomb effects also impact the acoustic oscillation spectrum. We confirm the well-known result that as the mass of a star decreases, the electrostatic interactions between particles become relevant. We found that their impact on stellar oscillations increases with decreasing mass, and for the stars with the lowest masses ( M ≲ 0.6 M⊙ ), it is shown that Coulomb effects dominate over partial ionization processes producing a strong scatter on the acoustic modes. The influence of Coulomb interactions on the sound-speed gradient profile produces a strong oscillatory behaviour with diagnostic potential for the future.